(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides theoretical information about the importance of the monologue in the literary work and its place in the construction of the work, which is considered one of the important issues in literary studies. Also, detailed information is given about the novel "Ota" by Ulugbek Hamdam, which was used in the research of monologues and its types. In addition, excerpts from the novel "Ota" are given as an example to explain the types of monologue separated by form and content.